TEACHING FOREIGN LANGUAGE: THEORY AND METHODOLOGY - To‘raqulova , Dilafro‘z; Baxranova , Zulfiya (Innovative Development in Educational Activities, 2023)
The methodology and theory of teaching foreign languages are the focus of the research. The article defines terms related to cross-cultural communication, foreign language teaching (FLT), conventional and current approaches to teaching. The study’s authors view the project teaching technique as one of the most successful techniques for teaching foreign languages.